Incomplete synthesis of N-glycans in congenital dyserythropoietic anemia type II caused by a defect in the gene encoding alpha-mannosidase II. - Fukuda, M N (1990)
Congenital dyserythropoietic anemia type II, or hereditary erythroblastic multinuclearity with a positive acidified-serum-lysis test (HEMPAS), is a genetic anemia in humans inherited by an autosomally recessive mode. The enzyme defect in most HEMPAS patients has previously been proposed as a lowered activity of N-acetylglucosaminyltransferase II, resulting in a lack of polylactosamine on proteins and leading to the accumulation of polylactosaminyl lipids. A recent HEMPAS case, G.C., has now been analyzed by cell-surface labeling, fast-atom-bombardment mass spectrometry of glycopeptides, and activity assay of glycosylation enzymes. Significantly decreased glycosylation of polylactosaminoglycan proteins and incompletely processed asparagine-linked oligosaccharides were detected in the erythrocyte membranes of G.C. In contrast to the earlier studied HEMPAS cases, G.C. cells are normal in N-acetylglucosaminyltransferase II activity but are low in alpha-mannosidase II (alpha-ManII) activity. Northern (RNA) analysis of poly(A)+ mRNA from normal, G.C., and other unrelated HEMPAS cells all showed double bands at the 7.6-kilobase position, detected by an alpha-ManII cDNA probe, but expression of these bands in G.C. cells was substantially reduced (less than 10% of normal). In Southern analysis of G.C. and normal genomic DNA, the restriction fragment patterns detected by the alpha-ManII cDNA probe were indistinguishable. These results suggest that G.C. cells contain a mutation in alpha-ManII-encoding gene that results in inefficient expression of alpha-ManII mRNA, either through reduced transcription or message instability. This report demonstrates that HEMPAS is caused by a defective gene encoding an enzyme necessary for the synthesis of asparagine-linked oligosaccharides.